Determinação de resíduos de pesticidas em solo de lavoura de arroz irrigado empregando QuEChERS modificado e LC-MS/MS - Martins, Gisele Lutz (2010)
The use of pesticides and their residues have become a problem due to possible contamination of soil, impacting on the environment and causing trouble to public health. In this research, an analytical method was optimized and validated to determine the residues of thiamethoxan, imazapic, imazethapyr, clomazone, propiconazole, fipronil and trifloxystrobin in soil from rice paddy field, applying a modified QuEChERS extraction method and Liquid Chromatography coupled to tandem Mass Spectrometry (LC-MS/MS) with Electrospray ionization source in ESI (+/-) mode. The modified QuEChERS method developed consisted of an initial extraction step using 5.0 g of soil into which 20 mL of saturated solution of calcium hydroxide pH 12.0 and 10 mL of acetonitrile were added, followed by a partition step after the addition of a mixture of anhydrous salts (4.0 g of magnesium sulfate and 3.0 g of sodium chloride). After this, a step for adjustment of the pH to 3.0 by adding 390 μL of 6 mol L-1 HCl, followed by centrifugation at 3900 rpm for 10 min. A clean-up step was then conducted with 250 mg of magnesium sulfate in 2 mL of extract, followed by LC-MS/MS analysis. After the optimization of the extraction and determination parameters the method was validated evaluating the analytical curve, linearity, LOD, LOQ, precision (repeatability and intermediate precision) and accuracy. Calibration curves presented linearity between 0.2 and 20.0 μg L-1 for propiconazole and 1.0 and 100.0 μg L-1 for thiamethoxan, imazapic, imazethapyr, clomazone, fipronil and trifloxystrobin, with determination coefficients greater than 0.99. The values of the method LOQ were 0.4 μg kg-1 for propiconazole and 2.0 μg kg-1 for the others pesticides. The method showed good precision, with RSD values < 20%, and good accuracy, with recoveries between 70 and 120% for most compounds. Concerning the Matrix Effect for all compounds evaluated, this was compensated by using calibration curves prepared in the matrix extract for quantification. The optimized method showed as major advantages: speed, simplicity, low cost, low consumption of organic solvents, besides the simplification of slow and laborious steps usually employed in traditional methods for extraction of pesticides in soil. The method was considered suitable for analysis of pesticide residues in soil from rice paddy fields, since all the validation parameters were within the limits suggested for validation of chromatographic methods. After the validation, the method was applied for determination of residues of these pesticides in soil samples from an experiment carried out at the UFSM Campus, revealing great efficience.